Detection of protein stoichiometric phosphorylation using Phos-tag SDS-PAGE - Minh Thu, Doan; Minh Viet, Nguyen Thi; Kim Lien, Pham Thi (Vietnam Journal of Biotechnology, 2020)
Protein phosphorylation plays an important role in many cellular signalings which are relating to many diseases. Therefore, a variety of biochemical techniques has been developed to study protein phosphorylation in cells. Protein phosphorylation has traditionally been detected by radioisotope phosphate labeling of proteins with radioactive ATP. Phosphorylation site-specific antibodies are now available for the analysis of phosphorylation status at target sites. However, these antibodies cannot be used to detect unidentified phosphorylation sites. Recently, the Phos-tag technology has been developed to overcome the disadvantages and limitations of these methods. Phos-tag and its derivatives conjugated to biotin, acrylamide, or agarose, and can capture phosphate monoester dianions bound to serine, threonine, and tyrosine residues, in an amino acid sequence-independent manner. The grouping of the Phos-tag will alter the mobility of protein on the gel depending on the amount of serine, threonine or tyrosine which are phosphorylated. Here, we describe the method to detect the phosphorylation of Pop2 protein, one of the exonucleases in the Ccr4-Not complex regulating the shortening of poly(A) tail of mRNAs using phosphate affinity Phos-tag SDS-PAGE. We observed clear electrophoretic 04 shift bands of Pop2-3XFlag under unstressed conditions. This is the first study which observes Pop2 phosphorylation in normal culture conditions. This study showed the convenience and advantages of Phos-tag SDS-PAGE for research on molecular mechanisms regulating the function of protein.